INOCULAÇÃO DE BACTÉRIAS SOLUBILIZADORAS DE FOSFATO E FIXADORAS DE NITROGÊNIO EM PASTAGEM - TENÓRIO, Kamila de Paula; ROCHETTI, Ana Carolina Alves; MACHADO, Dayane Camargo; DEZAN, Iris Mendes Namizaki; DA CUNHA, Julia Souza Pires; DE SOUZA, Beatriz Freitas (ANAIS DO ENIC, 2023)
-